METAMORFOSIS GERAKAN ARAH BARU INDONESIA MENJADI PARTAI GELOMBANG RAKYAT INDONESIA DI PROVINSI BALI - -, Hizkia; -, Bandiyah; Mahaswari Jayanthi Mertha, Anak Agung Sagung Mirah (Jurnal Nawala Politika, 2021)
This study aims to provide an overview of the metamorphosis process of Garbi into the Partai Gelora Indonesia in Bali Province. The theory used in this research is the Political Process Theory by McAdam. According to McAdam, there are three factors that determine the success of a social movement, namely organization strength, cognitive liberation, and political opportunities. This study used descriptive qualitative method. The findings of this study are first, that the existence of local political elites makes it easier for these elites to organize Garbi into the Partai Gelora Indonesia. Second, Garbi success made Garbi cadres want a broader movement by forming the Partai Gelora Indonesia. The results of the 2019 Election in Bali also fostered self-confidence to form the Partai Gelora Indonesia. Third, the existence of conflict within the Partai Keadilan Sejahtera (PKS) is an opportunity for the formation of the Partai Gelora Indonesia. Keywords: Movement Metamorphosis, Garbi, Partai Gelora Indonesia